Oblique Lumbar Interbody Fusion Combined With Anterolateral Fixation and Cement Augmentation for the Treatment of Degenerative Lumbar Diseases in the Elderly Population: A Retrospective Study - Weiqi Han; Lei He; Fei Wang; Xiaofeng Zhao; Cong Jin (Orthopaedic Surgery)
ABSTRACT Objectives Cage subsidence is a common complication of oblique lumbar interbody fusion (OLIF), particularly in elderly patients with osteoporosis or osteopenia. While bilateral pedicle screw fixation (BPS) is effective in reducing subsidence, it is associated with longer operative times, increased blood loss, and greater tissue trauma. In contrast, anterolateral fixation (AF) is less invasive but linked to higher subsidence rates. Ensuring both minimal invasiveness and adequate stability in OLIF‐assisted fixation remains a significant challenge. This study aimed to evaluate the efficacy of combining AF with cement augmentation (AF + CA) in reducing cage subsidence and improving clinical outcomes compared with AF and BPS. Methods A retrospective analysis was conducted on 138 elderly patients with degenerative lumbar diseases treated with OLIF. Patients were divided into three groups: AF + CA (32 patients), AF (32 patients), and BPS (74 patients). Clinical and radiographic outcomes were compared among the groups, and logistic regression analyses were performed to identify risk factors for cage subsidence after OLIF. Results At 1 year postoperatively, the disc height of the AF + CA group was significantly greater than that of the AF group. The cage subsidence rate in the AF + CA group was 24.3%, significantly lower than that in the AF group (48.8%, p < 0.05) and comparable to the BPS group (30.4%). Survivorship curve analysis showed better outcomes in reducing cage subsidence in the AF + CA group compared with the AF group, with no significant difference between the AF + CA and BPS groups. Compared with the AF + CA and BPS groups, the AF group had significantly higher grades and severity of cage subsidence. Fusion rates at 1 year were 91.9% in the AF + CA group, 90.2% in the AF group, and 95.1% in the BPS group, with no significant differences. The AF + CA group had significantly shorter operative times, less intraoperative blood loss, lower VAS scores at 3 days and 1 year postoperatively, and lower ODI scores at 3 days and 3 months compared with the BPS group. Multivariate regression analysis revealed that AF was a significant risk factor for cage subsidence, with an odds ratio of 3.399 compared with AF + CA. Conclusions AF + CA effectively reduces cage subsidence in OLIF surgeries, offering results comparable to BPS while providing advantages such as shorter surgical time, reduced blood loss, and improved early postoperative outcomes. AF + CA is a viable alternative, especially for elderly patients with comorbidities who may not tolerate the longer operative durations or greater blood loss associated with BPS.